2007
DOI: 10.4219/jaa-2007-553
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation of Learning and Academic Delay of Gratification: Gender and Ethnic Differences Among College Students

Abstract: Self-regulated learners engage in self-generated thoughts, actions, and feelings while pursuing academic goals. The most successful learners use appropriate learning strategies and maintain high levels of motivation. Few studies on the self-regulation of learning have examined individual differences such as gender and ethnicity among college students. The study examined gender and ethnic differences in the relationships between academic performance, self-regulation, motivation, and delay of gratification using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
102
2
25

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(141 citation statements)
references
References 17 publications
12
102
2
25
Order By: Relevance
“…Descriptive analyses showed that females reported higher tendencies of academic delay of gratification than males. This finding is in line with the findings reported by Bembenutty and his colleagues (Bembenutty, 2007(Bembenutty, , 2009Bembenutty & Karabenick, 1998) using samples of college students. This finding is noteworthy since it suggests that males and females can show differences in the way they manage academic situations by remaining goal oriented and committed to tasks while facing distractions that are typical features of learning contexts.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Descriptive analyses showed that females reported higher tendencies of academic delay of gratification than males. This finding is in line with the findings reported by Bembenutty and his colleagues (Bembenutty, 2007(Bembenutty, , 2009Bembenutty & Karabenick, 1998) using samples of college students. This finding is noteworthy since it suggests that males and females can show differences in the way they manage academic situations by remaining goal oriented and committed to tasks while facing distractions that are typical features of learning contexts.…”
Section: Discussionsupporting
confidence: 83%
“…This relationship can be explained within the framework of the self-regulated learning theory because academic delay of gratification has commonly been conceptualized as involving successful self-regulated learning (Bembenutty & Karabenick, 1998;Zimmerman, 1998). According to Bembenutty (2007Bembenutty ( , 2009, successful self-regulated learners engage in academic delay of gratification by deferring attractive activities in order to achieve long-term goals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations